Evaluation of a cassava germplasm collection for reaction to three major diseases and the effect on yield - Fokunang, C.N.; Akem, C.; Dixon, A.; Ikotun, T. (2000)
Thirty-five cassava (Manihot esculenta Crantz) genotypes from the International Institute of Tropical Agriculture (IITA), germplasm collection were planted in May 1992 under natural disease infection conditions, at the IITA field plots at Ibadan, Nigeria. The genotypes were evaluated at monthly intervals for six months, for incidence and severity of cassava anthracnose disease (CAD), cassava bacterial blight (CBB) and African cassava mosaic virus (ACMV). The effect of the pathogens on yield was also evaluated twelve months after planting (MAP). CAD, CBB and ACMV incidence and severity were significantly different (P<0.05) among the cassava genotypes at 3 and 6 months after planting. ACMV incidence and severity reached the maximum levels at 3 MAP while CAD and CBB had a low incidence and severity at that period but exhibited a high disease symptom expression at 6 MAP. Yield parameters (plant stand, tuber number, tuber weight and tuber dry matter) differed significantly (P<0.05) between the cassava genotypes. ACMV and CBB severity was negatively correlated with tuber number (r = −0.54 and r = −0.62 respectively). CAD severity was negatively correlated with tuber number (r = −0.46) and tuber weight (r = −0.63). Percentage dry matter was significantly correlated with ACMV severity (r = 0.71), CBB severity (r = 0.63) and CAD severity (r = 0.42). There was also a significant correlation between CBB and ACMD severity (r=0.46) and CBB and CAD severity (r=0.62). Tuber number and yield were significantly correlated (r=0.60), while% dry matter content and root rot showed a significant negative correlation (−0.42).